2006
DOI: 10.1080/15438620600985902
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive and Sensorimotor Performance in Parkinson's Disease

Abstract: We explored the effects of random whole-body vibration on leg proprioception in Parkinson's disease (PD). In earlier studies it was found that this treatment leads to improved postural control in these patients. Thus, one could speculate that these effects result from modified proprioceptive capabilities. Twenty-eight PD patients were subdivided in one experimental and one control group. Proprioceptive performance was analyzed using a tracking task basing on knee extension and flexion movements. Treatment cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 55 publications
3
49
0
3
Order By: Relevance
“…Both studies were performed by applying five sets of 60 seconds each, at 6 Hz, employing stochastic vibration which was one of the key features advocated by the authors. 5 However, more recently, significant effects on Parkinsonian patients have been reported using nonstochastic vibration. 4 These authors showed the effect of 25 Hz stimulation (twice per day, 15 min./each) for 3 weeks which produced an improvement in a set of motor tests (Tinetti balance score, 6 gait velocity, stand-walk-sit test, UPDRS III ), although similar results were seen with conventional rehabilitation therapy (relaxation, occupational therapy, etc.).…”
mentioning
confidence: 99%
“…Both studies were performed by applying five sets of 60 seconds each, at 6 Hz, employing stochastic vibration which was one of the key features advocated by the authors. 5 However, more recently, significant effects on Parkinsonian patients have been reported using nonstochastic vibration. 4 These authors showed the effect of 25 Hz stimulation (twice per day, 15 min./each) for 3 weeks which produced an improvement in a set of motor tests (Tinetti balance score, 6 gait velocity, stand-walk-sit test, UPDRS III ), although similar results were seen with conventional rehabilitation therapy (relaxation, occupational therapy, etc.).…”
mentioning
confidence: 99%
“…Although the methods of applying WBV among these studies are variable, shortterm improvements in balance and motor function were documented after WBV. The mechanisms of these improvements are unknown but it possible that vibration stimuli enhance sensory processing in individuals in PD [8,9,26]. Another possibility is that WBV promotes activation of dopaminergic neurons, as has been shown in animal models [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that motor deficits in PD may be directly related to the underlying mismatch of proprioceptive feedback and peripheral discharge for adequate balance reactions [5][6][7][8]. However, there is conflicting evidence in the literature as to whether proprioceptive deficits in PD are due to faulty peripheral or central pathways [9]. In addition, physiological evidence has yet to show that proprioceptive disturbances exist because of defective muscle spindle sensitivity or discharge [10].…”
Section: Introductionmentioning
confidence: 96%
“…Ces variations dans les protocoles utilisés s'expliquent en partie par les différences dans les objectifs cherchés par l'utilisation des plateformes vibrantes. Ainsi, les études destinées à améliorer la posture et la marche des malades parkinsoniens utilisent volontiers de faibles fréquences de vibration, inférieures à 10 Hz [3,4] alors que chez des femmes ménopausées la recherche d'une amélioration de la force musculaire fait généralement appel à des fréquences de vibration plus élevées, de 35 à 40 Hz [5,6]. Les caractéristiques des principales plateformes utilisées au cours d'études impliquant des sujets âgés figurent dans le tableau I.…”
Section: Une Ou Des Plateformes Vibrantes ?unclassified
“…Les auteurs notaient une amélioration de la stabilité posturale spontanée dans le groupe entraîné sur plateforme vibrante, suggérant que ce dispositif pouvait représenter une méthode additionnelle dans la rééducation des patients parkinsoniens [3]. Cette amélioration du contrôle postural chez les malades parkinsoniens serait indépendante des capacités proprioceptives [4]. La même équipe a évalué l'impact des vibrations corporelles totales sur les symptômes moteurs des malades parkinsoniens.…”
Section: Intérêt Des Plateformes Vibrantes Au Cours De La Maladie De unclassified